2009
DOI: 10.1186/1465-9921-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term gas exchange characteristics as markers of deterioration in patients with cystic fibrosis

Abstract: Background and AimIn patients with cystic fibrosis (CF) the architecture of the developing lungs and the ventilation of lung units are progressively affected, influencing intrapulmonary gas mixing and gas exchange. We examined the long-term course of blood gas measurements in relation to characteristics of lung function and the influence of different CFTR genotype upon this process.MethodsSerial annual measurements of PaO2 and PaCO2 assessed in relation to lung function, providing functional residual capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
0
21
2
6
Order By: Relevance
“…In our study group, P aO 2 (mean of 81.07 Ϯ 23.50 mm Hg) approximated the lowest limit defining normal oxygenation in children, that is 80 mm Hg. 24 In this context, higher P aCO 2 in patients with high exacerbation risk may be linked to an attenuated ventilatory response to the metabolic demand of O 2 consumption. Taking this hypothesis a step further, we speculate that diminished ventilatory response may predispose patients to development of clinically relevant exacerbations due to a failure to compensate for an increased ventilatory demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study group, P aO 2 (mean of 81.07 Ϯ 23.50 mm Hg) approximated the lowest limit defining normal oxygenation in children, that is 80 mm Hg. 24 In this context, higher P aCO 2 in patients with high exacerbation risk may be linked to an attenuated ventilatory response to the metabolic demand of O 2 consumption. Taking this hypothesis a step further, we speculate that diminished ventilatory response may predispose patients to development of clinically relevant exacerbations due to a failure to compensate for an increased ventilatory demand.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of arterialized capillary blood was preferred to arterial puncture or catheterization because it is technically simpler and less likely to result in serious complications; research has shown that this method provides sufficiently accurate measurements of P aO 2 and P aCO 2 . 24 Airway resistance was measured by the interrupter technique; this simple test, which requires only passive cooperation, provides an accurate estimate of airway resistance. 25 Home overnight S pO 2 monitoring was performed within 3 nights of entering the study.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement techniques have been described in detail previously. [8][9][10]37 All values were expressed by z-transformation in SD scores (SDS), based on gender-and age-specific regression equations. 38,39 Details regarding measurement techniques and clinical evidence of these target parameters are given in the online data supplement.…”
Section: Lung Function Testingmentioning
confidence: 99%
“…3 Clinically, CF is characterized by elevated sweat chloride concentration, exocrine pancreatic insufficiency, male infertility and progressive obstructive lung disease, the latter being the primary cause of mortality. 4,5 The respiratory disease progression in CF is expressed by various pulmonary dysfunctions, [6][7][8][9][10] such as ventilation inhomogeneities, 8,11 pulmonary hyperinflation, 9,12 bronchial obstruction, trapped gas and gas exchange disturbances, 10 most of them occurring early in life, 7,12,13 and progressing even in the absence of clinical signs and symptoms. 11,14,15 Owing to the great phenotypic variability in lung disease even observed among patients carrying the same CFTR genotype, several association studies have been conducted to find modifying genetic factors and to study their influence on CF disease outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation